Solubility and Partition Coefficient of Salicylamide in Various pH Buffer Solutions - Dewi Isadiartuti; Noorma Rosita; Esti Hendradi; Firdausiah Fania Dwi Putri Putri; Frida Magdalena (Indonesian Journal of Chemistry, 2021)
The solubility and partition coefficient are essential physicochemical parameters in developing a pharmaceutical dosage form of medicine. In addition, these parameters help to predict the absorption of an active compound in oral or topical dosage forms. Salicylamide, an active ingredient available in oral and topical dosage forms, is a weak acid (pKa 8.2) and is sparingly soluble in water. Meanwhile, its solubility and partition coefficients are influenced by the pH of the environment. The Henderson-Hasselbalch equation is used to predict solubility-pH and partition-pH profiles at various pH solutions. This study aims to determine salicylamide's solubility and partition coefficient in various pH (2–11). Both tests were carried out in various pH buffer solutions (at a concentration of 0.02 M and 0.2 ionic strength) in a water bath shaker at a temperature of 37 ± 0.5 °C. In addition, the salicylamide content was determined using the UV spectrophotometer method at the maximum wavelength at each pH. The results showed that the solubility increased at pH 2–10, while the partition coefficient value decreased. On the other hand, at pH 11, there was an increase in the number of ionized species, but the solubility decreased.